2017
DOI: 10.20319/mijst.2017.33.2435
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Flow Rate on the Removal of Copper, Lead and Nickel From Solutions in Electrodialysis Process

Abstract: In electrodialysis (ED)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…The results shown in Figure 5a revealed that HM concentrations higher than 30 mg/L negatively affect the process in terms of HM removal efficiency. The results obtained from this work showed higher HM removal efficiencies (above 98%) for ED than those reported in the literature [8,12,14,35]. According to the mass balance evaluation, only 1-10% of the removed HMs was transferred to the concentrate compartment.…”
Section: Impact Of the Hm Feed Concentrationcontrasting
confidence: 48%
See 1 more Smart Citation
“…The results shown in Figure 5a revealed that HM concentrations higher than 30 mg/L negatively affect the process in terms of HM removal efficiency. The results obtained from this work showed higher HM removal efficiencies (above 98%) for ED than those reported in the literature [8,12,14,35]. According to the mass balance evaluation, only 1-10% of the removed HMs was transferred to the concentrate compartment.…”
Section: Impact Of the Hm Feed Concentrationcontrasting
confidence: 48%
“…It is a challenging task to remove such dissolved contaminants, and current technologies often need to be operated in multiple stages to achieve effective removal. Current treatment technologies for the removal of HMs and other compounds include adsorption [5], flocculation, ion exchange [6][7][8], membrane filtration such as nanofiltration (NF) and reverse osmosis (RO) [9][10][11] and electromembrane processes such as electrodialysis (ED) [12][13][14], bipolar membrane electrodialysis (BMED) [15,16], and electrodeionization (EDI) [17,18]. The limitations of these technologies are their high operating costs and only partial removal, especially for marginally polluted brackish groundwater/surface water or industrial effluents.…”
Section: Introductionmentioning
confidence: 99%